2016
DOI: 10.3400/avd.oa.16-00082
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Surgical Treatment with In Situ Graft Reconstruction for Secondary Aorto-Enteric Fistula

Abstract: Objectives:The optimal surgical management for secondary aorto-enteric fistula (sAEF) is controversial. Here, we report the long-term outcomes of a surgical treatment with in situ graft reconstruction for sAEF that was performed at our hospital. Methods: Between 2009 and 2012, 10 consecutive patients (8 males, 2 females, mean age 75.9 years) with sAEF were surgically treated with in situ graft reconstruction. Perioperative and long-term outcomes were reviewed retrospectively by medical records. Results: Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…6) Some reports have suggested the existence of herald bleeding, which is a characteristic warning sign of this disease. 1,7) Song et al suggested that the frequency of herald bleeding was an average of 3.6 episodes and that the time between the initial herald bleeding and massive exsanguination ranged from 5 h to 5 months (median, 4 days, with over 50% of cases being longer than 3 days). 8) The management of SAEFE varies and is dependent on the patient s condition, with complete resection of the fistula being a standard treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…6) Some reports have suggested the existence of herald bleeding, which is a characteristic warning sign of this disease. 1,7) Song et al suggested that the frequency of herald bleeding was an average of 3.6 episodes and that the time between the initial herald bleeding and massive exsanguination ranged from 5 h to 5 months (median, 4 days, with over 50% of cases being longer than 3 days). 8) The management of SAEFE varies and is dependent on the patient s condition, with complete resection of the fistula being a standard treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Recent estimates of early post-operative mortality for these open surgical techniques vary widely, but remain high, in the range of 18-54% (8,9). As a result of these high mortality rates, endovascular interventions have grown in popularity to manage AEF patients.…”
Section: Mini-reviewmentioning
confidence: 99%
“…These massive hemorrhages may be life threatening. However, between 27% and 60% of SAEFs do not present with GI bleeding (1,6,8). The most common presentation for SAEF without GI bleeding is sepsis, which occurs in up to 80% of SAEF patients (some of these may have concomitant GI bleeding) (16,17).…”
Section: Clinical Presentation Of Aefmentioning
confidence: 99%
See 2 more Smart Citations